2018
DOI: 10.1016/j.ejvs.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Aortic Repair Follow up Protocol Based on Contrast Enhanced Ultrasound Is Safe and Effective

Abstract: The introduction of a CEUS based protocol for EVAR follow up was safe and effective and it was similar to the previous CTA based follow up protocol with regard to identification of endoleaks in a mid-term period. Moreover, CEUS allowed for 90% reduction of CTA, thereby decreasing radiation exposure for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…Our series showed a 1.7% 30-day mortality rate and a 7.0% long-term mortality rate, most of which were not related to AAA [6,17]. Following current guidelines, follow-up with CTA was done paying special attention to aneurysm size progression and endoleaks [29,30]. However, because of concerns of repeated exposure to radiation and nephrotoxic contrast, we started to include DUS surveillance during long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our series showed a 1.7% 30-day mortality rate and a 7.0% long-term mortality rate, most of which were not related to AAA [6,17]. Following current guidelines, follow-up with CTA was done paying special attention to aneurysm size progression and endoleaks [29,30]. However, because of concerns of repeated exposure to radiation and nephrotoxic contrast, we started to include DUS surveillance during long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of concerns of repeated exposure to radiation and nephrotoxic contrast, we started to include DUS surveillance during long-term follow-up. Some studies have reported that DUS showed similar detection of endoleaks as CT as well as a lower cost and avoidance of the ionizing radiation and contrast [10,12,30].…”
Section: Discussionmentioning
confidence: 99%
“…The CEUS presents detailed vascular morphology and enables real-time quantification of blood flow [34], which in some studies resulted in a higher specificity than that of CTA in endoleak classification [35]. In a recent retrospective study by Chisci et al The CEUS was used as a reference method of follow-up [36]. In their material 318 CEUS examinations were performed with no procedure-related complications and allowed for 90% reduction in the number of CTAs, thereby reducing radiation exposure for patients.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…21). As a result, CEUS allows a reduction of the number of CT angiography in surveillance and can reduce radiation hazard and complication related to iodinated contrast agent (7576). In most recently updated guidelines from European Federation of Societies for Ultrasound in Medicine and Biology, CEUS using this new USCA is recommended not only for the detection and characterization of endoleak but also for the follow-up of AAA endoleak with the strongest level of recommendation (77).…”
Section: Issues Related To Radiation and Contrast Materialsmentioning
confidence: 99%